2017
DOI: 10.1108/jkm-09-2016-0394
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the universality of knowledge management practices

Abstract: Purpose This paper aims to contribute to the emerging discussion on the contextualization of knowledge-oriented research by examining the universality of knowledge management (KM) practices. Knowledge is a firm’s most valuable resource, and KM, or the ability to leverage knowledge resources, constitutes the base for the firm’s competitive advantages. Design/methodology/approach A theorized ten-fold conceptualization of KM practices is tested on a sample of 622 firms from four countries (Finland, Spain, China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 112 publications
3
91
1
5
Order By: Relevance
“…Along this vein, research on strategic renewal has also highlighted the importance of knowledge management (KM), which plays a crucial role in a firm's overall ability to renew its competencies, and, therefore, for adapt to environmental change and sustain competitive advantage (Pérez-Pérez and Hernández-Linares 2020; Lengnick-Hall and Inocencio-Gray 2013; Kianto 2011). KM can be defined as a set of activities, initiatives, and strategies that companies use to generate, store, transfer, and apply knowledge within and between organizations (Hussinki et al 2017;Calvo-Mora et al 2016;Jayasingam et al 2013;Zack et al 2009) under the influence of their history, people, interests, and actions that have been institutionalized in the organizations (Kostova 1999). The newer strategic renewal literature recognizes KM as a synergistic link/capability of strategic flexibility (Lin and Wu 2014; Bamel and Bamel 2018), because cross-functional exchange of knowledge helps organizations quickly understand the changing environment, allowing the firm to plan organizational priorities and actions accordingly (Fernández-Pérez et al 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Along this vein, research on strategic renewal has also highlighted the importance of knowledge management (KM), which plays a crucial role in a firm's overall ability to renew its competencies, and, therefore, for adapt to environmental change and sustain competitive advantage (Pérez-Pérez and Hernández-Linares 2020; Lengnick-Hall and Inocencio-Gray 2013; Kianto 2011). KM can be defined as a set of activities, initiatives, and strategies that companies use to generate, store, transfer, and apply knowledge within and between organizations (Hussinki et al 2017;Calvo-Mora et al 2016;Jayasingam et al 2013;Zack et al 2009) under the influence of their history, people, interests, and actions that have been institutionalized in the organizations (Kostova 1999). The newer strategic renewal literature recognizes KM as a synergistic link/capability of strategic flexibility (Lin and Wu 2014; Bamel and Bamel 2018), because cross-functional exchange of knowledge helps organizations quickly understand the changing environment, allowing the firm to plan organizational priorities and actions accordingly (Fernández-Pérez et al 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, a hierarchical organisational structure may be less efficient in disseminating information compared to cross-functional teams (Hussinki et al, 2017). Empirical studies have shown that supports from senior management, employee empowerment, and power decentralisation are positively correlated to the successful implementation of knowledge management systems (Hussinki et al, 2017;Yang and chen, 2007).…”
Section: Organisational Structure (Os)mentioning
confidence: 99%
“…Knowledge represents a cumulative body of beliefs (Berkes et al, 2007), intellectual development (Hussinki et al, 2017), and cultural evolution (Green and Raygorodetsky, 2010). Knowledge can exists in various forms, including formal, informal, tacit, explicit, local, scientific, etc.…”
Section: Culture Knowledge (Ck)mentioning
confidence: 99%
See 2 more Smart Citations